ANALISIS BINGKAI BERITA TAMBANG ILEGAL DI KALIMANTAN TIMUR OLEH KALTIMKECE.ID - Widia Novi Ramadianti; Nurliah, S.Sos., M.I.Kom (PT. Media Akademik Publisher, 2024)
This research aims to find out and describe how Kaltimkece.id frames news related to illegal mining in East Kalimantan, especially in Muang Dalam. The object of this research is two news stories about illegal mining in Muang Dalam which were published in September 2021. This research uses the framing analysis method. The technique used to collect data is text analysis media. The analysis technique used in this research is Robert N. Entman's framing analysis model, and then it is dissected again using the social construction theory of mass media by Burhan Bungin. The research results show that Kaltimkece.id in its reporting selects issues and highlights reality. This research also shows how partial Kaltimkece.id is in reporting this issue.